miR-133b Downregulation Reduces Vulnerable Plaque Formation in Mice with AS through Inhibiting Macrophage Immune Responses - Cheng-Gen Zheng; Bing-Yu Chen; Ren-Hua Sun; Xiao-Zhou Mou; Fang Han; Qian Li; Hai-Jun Huang; Jing-Quan Liu; Yue-Xing Tu (Elsevier, 2019)
Atherosclerosis (AS) is a chronic inflammatory disease characterized by accumulating deposition of lipids in the arterial intima. Notably, macrophages participate centrally in the pathogenesis of this deadly disease. In this study, we established AS mouse models in order to investigate the effect of microRNA-133b (miR-133b) on vulnerable plaque formation and vascular remodeling in AS and explore the potential functional mechanisms. The expression of miR-133b was altered or the Notch-signaling pathway was blocked in the AS mouse models in order to evaluate the proliferation, migration, and apoptosis of macrophages. It was observed that miR-133b was upregulated in AS, which might target MAML1 to regulate the Notch-signaling pathway. AS mice with downregulated miR-133b or inhibited Notch-signaling pathway presented with a reduced AS plaque area, a decreased positive rate of macrophages, and an increased positive rate of vascular smooth muscle cells. Moreover, Notch-signaling pathway blockade or miR-133b downregulation inhibited the macrophage viability and migration and accelerated the apoptosis. This study provides evidence that downregulated miR-133b expression may inhibit the immune responses of macrophages and attenuate the vulnerable plaque formation and vascular remodeling in AS mice through the MAML1-mediated Notch-signaling pathway, highlighting miR-133b as a novel therapeutic target for AS. Keywords: microRNA-133b, atherosclerosis, Notch-signaling pathway, macrophage, plaque formation